Correlation Between Peripheral Blood Biomarkers and Efficacy of PD-1/PD-L1 Inhibitors Treatment on Lung Cancer - KE Ping (Magazine House of Cancer Research on Prevention and Treatment, 2021)
Objective To investigate the predictive and guiding significance of peripheral blood biomarkers on the therapeutic effects of PD-1/PD-L1 inhibitor treatment on lung cancer patients. Methods We collected the data of 200 lung cancer patients treated with PD-1/PD-L1 inhibitors treatment, including clinical indicators, peripheral blood indicators, efficacy indicators and survival indicators. Results The DCR of patients with non-hepatic metastasis, immune combined chemotherapy, NLR≤2.81 and LDH≤202.5 u/L was higher (P < 0.05). The AUC value of NLR combined with LDH predicting DCR was 0.698 (P < 0.05). Univariate analysis showed that non-hepatic metastasis, first-line immunotherapy, immunotherapy combined with chemotherapy and LDH≤202.5 u/L were related to PFS (P < 0.05). Multivariate analysis showed that the patients with non-hepatic metastasis and LDH≤202.5 u/L had longer PFS (P < 0.05). The significant decrease of NLR and LDH after two cycles of immunotherapy indicated the effectiveness of immunotherapy (P < 0.05). Conclusion NLR≤2.81, LDH≤202.5 u/L, non-hepatic metastasis and immunotherapy combined chemotherapy are positively correlated with immunotherapy efficacy. Non-hepatic metastasis and LDH≤202.5 u/L are independent prognostic factors of the patients treated with immunotherapy. The changes of peripheral blood NLR and LDH are related to the efficacy of PD-1/PD-L1 inhibitors treatment.